PWE-041 Obesity is associated with improved survival in surgically resected oesophageal cancer. (28th May 2012) - Athwal, T S; Love, S; Bruce, S; Page, R; Hartley, M; Howes, N
Abstract : Introduction: Obesity is an increasing health burden in the western world and a known risk factor for oesophageal cancer. The aim of this study was to determine the impact of obesity on circumferential resection margin (CRM), lymph node yield (LNY) and survival among a 10 year cohort of surgically resected oesophageal cancer patients. Methods: All patients who underwent transthoracic oesophagectomy for histologically proven adenocarcinoma or squamous cell carcinoma, performed at a supra-regional upper GI cancer centre, were registered on a prospective database between 2002 and 2012. Total LNY, CRM and survival was compared between different BMI groups: normal (18.5–24.9), overweight (25–30), and obese (>30). Patients who were malnourished prior to surgery were excluded from the analysis. Results: A total of 482 consecutive patients underwent oesphagectomy during the study period, of which the complete dataset was available for 441 (91%); normal (155), overweight (177) and obese (91). The median lymph node yield was 16 (IQR 11–22), normal 15 (10–23), overweight 17 (12–23) and obese 15 (10–21), with no significant difference seen between the three groups (p=0.4565, χ 2 test). The CRM was involved in 30 (27%) of the obese patients compared to 55 (31%), 54 (35%) and of overweight, healthy patients respectively (p=0.0615, χ 2 test). Conclusion: Obesity appears to confer a survival advantage in patients undergoing surgical resection for oesophageal cancer. Interestingly, there appeared to be a trend towards an uninvolved CRM in obese patients but no significant impact on the lymph node yield. Competing interests: None declared.